Editorial for the Special Issue “The Role of Dietary Bioactive Compounds in Human Health” in Molecules - Bin Du; Baojun Xu (Molecules)
The prevalence of chronic diseases, such as cardiovascular disease, diabetes, chronic obstructive pulmonary disease and severe mental health disorders, has been constantly increasing over the last two decades [...]